THE TECNOLOGY OF TIDAL TRAP BARRIER FISHING GEAR IN VILLAGE ANAK SETATAH WEST RANGSANG DISTRICT OF MERANTI ISLAND REGENCY RIAU PROVINCE - Muhammad Reza; Arthur Brown; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in May 2015 in the village of Anak Setatah District of Western Rangsang of Meranti Island Regency Province of Riau. The aim of this study is analyze aspects relating to technological aspects of environmental friendliness, fishing operations management and business feasibility. The method used is a survey method. Results obtained environmental friendliness of 29.7 means environmentally friendly. The results of the feasibility namely Benefit cost ratio of 3.5, the financial rate of return of 11%, and a payback period of 9.6 months.Keywords: Splint, environmental friendliness, fishing operation, business feasbility